1981
DOI: 10.1055/s-2008-1034583
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin, Transferrin, Haptoglobin, and Iron in Middle- and Long-Distance Runners, Elite Rowers, and Professional Racing Cyclists*

Abstract: Serum ferritin, transferrin, haptoglobin, and iron were measured in well-trained middle- and long-distance runners, elite rowers of the West German national team, and professional racing cyclists during the summer training and the winter rest period. None of the male athletes examined, with the exception of the racing cyclists during the summer period, received oral or parenteral iron. The runners were found to have significantly lower ferritin (P less than 0.00001), iron (P less than 0.001), and haptoglobin v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
1
5

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 21 publications
9
57
1
5
Order By: Relevance
“…The incidence of 12% hematuria after the run seen in our study is more in tandem with that found in Israeli Air Force recruits (5%), 1 unlike the incidence of470% seen in hard core athletes like ultra marathoners, 3 long distance skiers or 45% in professional athletes. [9][10][11][12][13][14] All investigators have commented that post exertional hematuria subsides within 72 h. [2][3][4]12,16,18 However, 19% of our subjects had persistence of hematuria beyond 72 h, and three individuals continued to have hematuria beyond 14 days.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The incidence of 12% hematuria after the run seen in our study is more in tandem with that found in Israeli Air Force recruits (5%), 1 unlike the incidence of470% seen in hard core athletes like ultra marathoners, 3 long distance skiers or 45% in professional athletes. [9][10][11][12][13][14] All investigators have commented that post exertional hematuria subsides within 72 h. [2][3][4]12,16,18 However, 19% of our subjects had persistence of hematuria beyond 72 h, and three individuals continued to have hematuria beyond 14 days.…”
Section: Discussionsupporting
confidence: 72%
“…The incidence of post exercise hematuria varies from 5% as reported in Israeli Air Force recruits 1 to over 20% in trained athletes. [2][3][4] In 1910, Barach 5 reported proteinuria, granular casts and hematuria in marathon runners, which was later labeled as ''athletic pseudonephritis''.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that distance runners have compromised iron stores (4,8,14,22). In some cases, iron supplementation is required to prevent or correct anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, distance running has been associated with significant destruction of red blood cells (RBC) with RBC turnover being substantially higher in runners compared with untrained controls (29). Several groups have suggested that mechanical damage to RBC occurs as they pass through the capillaries of the foot during the footstrike phase (5,8,10,20,29). However, studies on athletes involved in sports in which foot impact does not occur have also found evidence of exercise-induced hemolysis.…”
mentioning
confidence: 99%
“…0 2-+ Fe3 + ------> Fe2+ + 0 2 Fe2+ + H20 2 ------> Fe3+ + O H ' + OH O2 " + H2 O2 > O2 + *OH + OH" Baixas concentrações séricas de ferro são encontradas em indivíduos treinados (Dufaux et alii., 1981). Com efeito, o treinamento físico está associado com redução do hematócrito e concentração plasmática de hemoglobina e ferro pois, é comum atletas perderem ferro durante o exercício intenso prolongado e ficarem anêmicos com o treinamento (Newhouse & Clement, 1988).…”
Section: Esquem Aunclassified